Multiphase deformation deduced from 3D construction and restoration: Implication for the hydrocarbon exploration in the mountain front of the Northern Tianshan. (November 2016) - Li, Yiquan; Wei, Dongtao; Chen, Zhuxin; Jia, Dong; Ma, Delong; Wang, Yanjun; Cui, Jian; Shen, Shuxin
Abstract: Three-dimensional (3D) modeling and restoration are powerful in describing the geological characteristics and kinematics which cannot be fully accomplished by the two-dimensional modeling methods. In this study, we applied 3D modeling and restoration to the Beisantai anticline along the mountain front of the Northern Tianshan. The Beisantai anticline shows an EW-trending structure in the shallow layers with NS-trending structures in the deep layers. The 3D seismic reflection data visualize the growth strata well, which record the evolution of the anticline and the influence of Cenozoic India-Asian collision. Our results suggest that a combination of multiple deformations of this anticline on different layers developed during different episodes. In addition, multiphase deformation and strain distribution along the eastern part of the northern Tianshan was implied. Combined with an analysis of the burial and hydrocarbon-generating history from borehole data, we proposed new potential exploration areas in this region and multistage tectonic effects for hydrocarbon accumulation. This work not only highlights our understanding of the structural decomposition of a multiphase structure associated with growth strata, but also the structural evolution of the northern Tianshan and the adjacent petroleum-producing Junggar Basin. Highlights: Multiphase deformation in the mountain front of the Northern Tianshan is revealed. Structure and strain are decomposed based on 3D structural modeling and restoration. The hydrocarbon accumulation history and favorable area in Beisantai are proposed.